ANALISIS KESULITAN BELAJAR SISWA PADA MATERI POKOK SISTEM INDRA MANUSIA (PENGLIHATAN, PENDENGARAN DAN PENGECAP) DI KELAS XI IPA MAN 1 STABAT - Silvia Adriani; Lazuardi Lazuardi (Jurnal Pelita Pendidikan, 2017)
This study aims to determine the students' learning difficulties from the experimental observations of human sensory, cognitive and learning indicators and factors that cause the learning difficulties in class XI of Science at MAN 1 Stabat at the year of learning 2015/2016. The study used descriptive quantitative design. Samples were taken by total sampling with 71 students. The technique of data collection used observation tests, diagnostic tests and questionnaires. The results show that the percentage of the students' learning difficulties from the highest to the lowest on cognitive aspects, they are C5, C6, C3, C4, C2 and C1 for amount 70.43%, 53.06%, 51.17%, 47.09%, 44, 72% and 34.51%. The Percentage of students' learning difficulties based on the indicators in the material of human sensory system are indicator (1) amount 65.26% categorized as very high, the indicator (2) amount 45.54% categorized as high, the indicator (3) amount 43.98% categorized as high and the indicator (4) of 53.93% categorized as very high. Internal and external factors that cause the learning difficulties of learning difficulties highest to lowest percentage are the subject matter (61.40%), the school environment (61.26%), instructional media (54.66%), intelligence (45.07%), motivation (43.48%), parents (42.69%), the environment (41.81%), psikiatik (41.19%), teachers (41.10%), interest (39.17%) and health (38.99%).Keywords: Cognitive Aspects, Human Sensory Systems, Learning Difficulties, , Learning Indicators